Cognitive distortion and its relation to the implications of violence in the drawings of middle school students - Athaeeb, Ass.Lecture Hayder Habeeb (Thi Qar Arts Journal, 2023)
: The current research aims to achieve the following objectives: 1- To know the level of cognitive distortion among middle school students.2- To know the level of violence indicators in students’ drawings.3- To know the correlation between cognitive distortion and violence indicators in students’ drawings. The research procedures were as follows: The researcher used in the current research (the descriptive correlational approach) as it suits the nature of the research and its variables, and the total research community consisted of (3580) students for the first intermediate grade affiliated to the Directorate of Education of Dhi Qar / Department of Education of Al-Rifai District, as the research tools were applied to a sample consisting of (400) male and female students, The researcher adopted a scale (cognitive distortion) prepared by (Al-Asadi, 2018), As for the scale (violence indicators), the researcher prepared it according to a number of educational and training lists, more clarification in Chapter Three, The researcher presented the two scales to a group of experts in the field of education, psychology, measurement, evaluation and psychological and educational guidance to detect the validity of the two scales items, The researcher used statistical methods (arithmetic mean, standard deviation, t-test for one sample, Pearson correlation coefficient), and the results of the current research confirmed the following: "There is cognitive distortion among middle school students, according to the result of the second goal there is an indication of violence in their drawings, As for the third goal, it showed that there is a correlation between (cognitive distortion and violence indicators among students).